Chromium supplementation in overweight and obesity: A systematic review and meta-analysis of randomized clinical trials - Onakpoya, I; Posadzki, P; Ernst, E (2013)
The increased prevalence of obesity has made the use of dietary supplements as weight reducing agents highly popular, but their efficacy has not been proven. One such supplement is chromium. The purpose of this review was to evaluate the evidence for or against the efficacy of chromium supplementation in overweight and obese individuals. Electronic searches were conducted in Medline, Embase, Amed and The Cochrane Library. The bibliographies of located articles were also searched. No age, gender or language restrictions were imposed. The reporting quality of identified randomized clinical trials (RCTs) was assessed using a methodological checklist adapted from the Consolidated Standard of Reporting Trials Statement and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Thirty-nine trials were identified and 20 were included. There were variations in reporting quality of included studies. A meta-analysis of 11 studies showed a statistically significant difference in weight loss favouring chromium over placebo (mean difference (MD): -0.50kg; 95% confidence interval (CI): -0.97, -0.03). There was a high statistical heterogeneity. Adverse events included watery stools, vertigo, headaches and urticaria. The evidence from available RCTs shows that chromium supplementation generates statistically significant reductions in body weight. The magnitude of the effect is small, and the clinical relevance is uncertain. Future trials should last at least 16 weeks and greater uniformity in the measuring and assessment tools for body composition is recommended. © 2013 International Association for the Study of Obesity.